DbAMEPNI: a database of alanine mutagenic effects for protein–nucleic acid interactions. (2nd April 2018) - Liu, Ling; Xiong, Yi; Gao, Hongyun; Wei, Dong-Qing; Mitchell, Julie C; Zhu, Xiaolei
Abstract: Protein–nucleic acid interactions play essential roles in various biological activities such as gene regulation, transcription, DNA repair and DNA packaging. Understanding the effects of amino acid substitutions on protein–nucleic acid binding affinities can help elucidate the molecular mechanism of protein–nucleic acid recognition. Until now, no comprehensive and updated database of quantitative binding data on alanine mutagenic effects for protein–nucleic acid interactions is publicly accessible. Thus, we developed a new d atab ase of A lanine M utagenic E ffects for P rotein-N ucleic Acid I nteractions (dbAMEPNI). dbAMEPNI is a manually curated, literature-derived database, comprising over 577 alanine mutagenic data with experimentally determined binding affinities for protein–nucleic acid complexes. It contains several important parameters, such as dissociation constant ( Kd ), Gibbs free energy change ( ΔΔG ), experimental conditions and structural parameters of mutant residues. In addition, the database provides an extended dataset of 282 single alanine mutations with only qualitative data (or descriptive effects) of thermodynamic information. Database URL : http://zhulab.ahu.edu.cn/dbAMEPNI